Wideband mirrored current source design based on differential difference amplifier for electrical bioimpedance spectroscopy. (9th February 2018) - Zhang, Fu; Teng, Zhaosheng; Zhong, Haowen; Yang, Yuxiang; Li, Jianmin; Sang, Jiangyan
Abstract: Wideband current sources that can work stable over a wide frequency range with large load variations are critical for the performance of electrical impedance spectrum (EIS) measurements. In this paper, we design a wideband mirrored current source (MCS) using two simple differential difference amplifiers (DDA) AD830. PSpice simulation and measurement were performed on load resistances from 100 Ω to 1500 Ω over the frequencies up to 1 MHz. The maximum variation of the output current is less than 0.5% over the whole bandwidth and the output impedance is 4.2 MΩ at 100 Hz and greater than 185 kΩ at 1 MHz. Moreover, less than 1% linearity error (the V IN versus the I OUT ) of the output current I OUT from 1 mA to 20 mA was achieved by sweeping the input voltage signal V IN from 0.1 V to 2 V at 100 Hz, 1 kHz and 10 kHz respectively. The DDA-based wideband MCS has high accuracy, linearity and simple structure, which may improve the performance of EIS measurements and other relevant applications.